A Transthoracic Ultrasound-Guided Needle Biopsy Provided the Diagnosis for a Synovial Sarcoma of the Pleura. (January 2023) - Palumbo, Maria Giovanna; Quarato, Carla Maria Irene; Lacedonia, Donato; Lucia, Dimitri; Simeone, Anna; Di Micco, Concetta; De Cosmo, Salvatore; Scioscia, Giulia; Foschino Barbaro, Maria Pia; Sperandeo, Marco
A case report is presented of a 72-year-old woman with monophasic synovial sarcoma of the buttocks, diagnosed four years before. The tumor was treated with surgical removal followed by radiotherapy. The patient regularly underwent follow-up examinations and the last chest computed tomogram (CT) showed a left-sided pleural mass and ipsilateral effusion. The patient was admitted in hospital to obtain a specific histological diagnosis before treatment of chest pathology was initiated. An ultrasound (US)-guided fine needle aspiration biopsy (FNAB) of the pleural lesion and US-guided thoracentesis with drainage of blood serum pleural fluid were performed. The pathological examination of the lesion revealed a definitive diagnosis of synovial sarcoma of the pleura. For pleural-based lesions, the diagnostic accuracy of US-guided biopsy is similar to that of CT-guided biopsy, with a lower complication rate, the absence of radiation exposure to patients, and a significantly reduced procedural time. The presence of pleural effusion creates a favorable acoustic window for US-guided biopsy of pleural lesion, which is useful for the diagnosis.